2016
DOI: 10.1097/igc.0000000000000833
|View full text |Cite
|
Sign up to set email alerts
|

A Real-Life Experience of Bevacizumab in Elderly Women With Advanced Ovarian Carcinoma

Abstract: Bevacizumab is feasible in patients older than 70 years with advanced ovarian carcinoma. More attention must be paid to elderly patients with baseline HTN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
1
7
1
Order By: Relevance
“…However, there was no prominent increase in the incidence of proteinuria, gastrointestinal perforation or other adverse events associated with bevacizumab. Another retrospective study that examined bevacizumab-containing therapy in ovarian cancer patients found that patients older than 70 years had a greater incidence of grade ≥3 hypertension as compared to those aged 70 years or younger (15). As compared to our current study, the incidence of adverse events reported for bevacizumab therapy in these other reports are inconsistent with regard to our findings.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, there was no prominent increase in the incidence of proteinuria, gastrointestinal perforation or other adverse events associated with bevacizumab. Another retrospective study that examined bevacizumab-containing therapy in ovarian cancer patients found that patients older than 70 years had a greater incidence of grade ≥3 hypertension as compared to those aged 70 years or younger (15). As compared to our current study, the incidence of adverse events reported for bevacizumab therapy in these other reports are inconsistent with regard to our findings.…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, the two age groups did not significantly differ in PFS or OS. Several previous reports have suggested that the efficacy of bevacizumab-containing therapy is similar in older and younger patients with ovarian cancer (15)(16)(17). Although these reports investigated treatment with bevacizumab in combination with other cytotoxic agents, the results are consistent with our study, which evaluated bevacizumab monotherapy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…17 In both ROSiA and AURELIA, baseline hypertension was substantially more common in older than in younger patients (70% vs 28% in ROSiA; 46% vs 13% in AURELIA). Furthermore, in AURELIA, the increased incidence of hypertension during treatment was also observed in the control arm (grade Q2: 14% in patients aged Q65 years vs 3% in patients G65 years).…”
Section: Discussionmentioning
confidence: 91%
“…Beinse et al (46) conducted a study among older ovarian cancer patients in order to assess the tolerance of bevacizumab and identify a subpopulation of patients with a high risk of severe adverse effects. The median age at first infusion of bevacizumab was 67.5 years.…”
Section: Bevacizumabmentioning
confidence: 99%